Effects of Anastrozole Combined with Shuganjiangu Decoction on Osteoblast-like Cell Proliferation, Differentiation and OPG/RANKL mRNA Expression - Ren, Yan; Han, Shu-yan; Li, Ping-ping (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: To investigate the effects of anastrozole combined with Shuganjiangu decoction on osteoblast-like cells. Methods: Human osteoblast-like cells MG-63 were cultured and divided into four groups: control, anastrozole, Shuganjiangu decoction (SGJGD), and anastrozole combined with SGJGD. Cell proliferation was investigated by MTT assay. Alkaline phosphatase (ALP) and osteocalcin, the indicators of cell differentiation, were evaluated by p-nitrophenylphosphate method and radioimmunoassay, respectively. Gene expressions of ALP, osteocalcin, osteoprotegerin (OPG) and receptor activator of nuclear factor kappa B ligand (RANKL) were examined by real-time PCR. Results: As evidenced by MTT assay, cell proliferation of MG-63 was inhibited by anastrozole, but stimulated with treatment of SGJGD alone and combined with anastrozole (P